Uso do solo e qualidade da água em microbacia urbana: estudo de caso bacia do rio dos cágados no estuário de Serinhaém - Cabral, Rafael Reis (2023)
The development of cities, from the beginning happened in conjunction with the use of water, the banks of rivers were the places where the process of agriculture and urbanization began, due to the proximity of such an important resource that is water. This occupation has generated changes in the physical, chemical and biological composition of water bodies. These changes compromise and restrict the various uses of water, in addition to requiring more expensive methods of treating and recovering water quality. In this context, the objective of this work was to verify the levels of metals and other parameters in the river basin of Cágados, as well as the possible origins from the different land uses in the basin. To fulfill this objective, an unsupervised classification of the area was carried out using clusters, which were analyzed and classified individually. The analyzed parameters were pH, Electrical Conductivity, Temperature, D.O., Salinity, B.O.D, total coliforms, thermotolerant coliforms, Chlorophyll-a, Al, Cd, Cr, Cu, Fe, Mn, Ni, P, Pb and Zn, which were compared with the values determined in CONAMA resolution 357/05 and CONAMA 454/12, and with other studies already published and then used the Spearman correlation method to verify their possible origins. Sampling showed a strong presence of Thermotolerant Coliforms, indicating contamination of the environment by the release of effluents, which may be causing health problems for the population in the region. The relationship between the metals demonstrates that they are immobile in the sediments, and have a probable natural origin with the exception of Zn, BOD and P, which have a possible anthropic origin related to urban and rural releases in the basin.